ABPA sans asthma: an entity to remember. Issue 11 (25th November 2022) - Nair, Avinash Anil; Vimala, Leena Robinson; Chandran, Divya; Gupta, Richa
Abstract : A male patient in his 20s presented with a cough and a small volume of haemoptysis that lasted a year. He had no other constitutional symptoms and a respiratory examination was suggestive of a consolidation. A chronic infection, such as tuberculosis, was suspected. The routine evaluation showed peripheral eosinophilia with raised serum total IgE. Sputum examination for tuberculosis was negative; hence, a high-resolution CT of the thorax was performed, which revealed bilateral bronchiectasis with high-attenuation mucus plugging. The imaging and blood profiles were in favour of allergic bronchopulmonary aspergillosis, but there was no history suggestive of asthma, and the pulmonary function test was normal. The patient underwent a skin prick test and an allergen-specific IgE test for Aspergillus fumigatus, and both were positive. His bronchoalveolar lavage cultures also grew A. fumigatus, and he responded well to antifungal therapy. This case illustrates the presentation of a rare entity—allergic bronchopulmonary aspergillosis sans asthma.